2018
DOI: 10.1590/1983-21252018v31n428rc
|View full text |Cite
|
Sign up to set email alerts
|

Emergence Rate of the Mexican Bean Weevil in Varieties of Beans From the Southwestern Amazon

Abstract: Common beans (Phaseolus vulgaris L.) are one of the most important protein sources worldwide. However, infestation by bruchids compromises the storage of these beans after harvest. The objective of this study was to determine the emergence rate of Zabrotes subfasciatus (Coleoptera: Chrysomelidae) in four P. vulgaris varieties (Carioca Pitoco, Enxofre, Gorgutuba Vermelho, and Rosinha) cultivated in the southwestern Amazon (State of Acre, Brazil). The grains from each variety were infested with 50 non-sexed adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The grain production chain requires suitable sanitary precautions owing to the occurrence of numerous pests that may cause economic damage, especially during the storage period, particularly in undeveloped countries such as Brazil (Lopes et al, 2018). Associated with this problem, several mites infest various materials, such as grains, dairy products, dried fruits, straw, and animal skin, that are produced and stored commercially; these are considered common contaminants in substrates where other arthropods also propagate (Hagstrum et al, 2013;Dhooria, 2016;Mullen and Oconnor, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The grain production chain requires suitable sanitary precautions owing to the occurrence of numerous pests that may cause economic damage, especially during the storage period, particularly in undeveloped countries such as Brazil (Lopes et al, 2018). Associated with this problem, several mites infest various materials, such as grains, dairy products, dried fruits, straw, and animal skin, that are produced and stored commercially; these are considered common contaminants in substrates where other arthropods also propagate (Hagstrum et al, 2013;Dhooria, 2016;Mullen and Oconnor, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…; Fabaceae) are legumes widely used for human consumption. They have an important social, economic, and nutritional role in countries like Brazil, where they are among the most widely consumed grains (Souza et al 2010;Oliveira et al 2013;Lopes et al 2016Lopes et al , 2018a.…”
Section: Introductionmentioning
confidence: 99%
“…Using genetically resistant varieties is an advantageous way of controlling bruchids because it maintains pests below the level of economic damage and does not require additional costs. Some studies have demonstrated the existence of cowpea genotypes resistant to C. maculatus and common bean genotypes resistant to Z. subfasciatus; the insects' reproductive development is used as a trait to characterize the source of resistance (Somta et al 2006;Cruz et al 2015;Lopes et al 2016Lopes et al , 2018a. The wide diversity of landrace beans grown by small farmers for decades in the southwestern Amazon region has been a source of resistance to bean weevils.…”
Section: Introductionmentioning
confidence: 99%